Penerapan Akuntansi Dan Penggunaan Informasi Akuntansi Pada UMKM Di Kecamatan Gerung - Ni Kadek Widya Puspa Rina; Ni Nyoman Yuliati; Agus Khazin Fauzi (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2024)
This study aims to determine the application of accounting and the use of accounting information in Micro, Small and Medium Enterprises (MSMEs) in Gerung District. This study took 86 MSMEs in Gerung District. The data used in this study is primary data obtained through the results of the questionnaire. The data analysis technique in this study is a qualitative descriptive analysis technique. The sampling technique in this study was to use the Random Sampling technique. The results showed that the majority, namely 69% of Micro, Small and Medium Enterprises (MSMEs) in Gerung District had implemented accounting such as recording sales, purchases, inventories, cash in, cash out, costs and salaries. Meanwhile, the financial reports made by several MSMEs are only profit/loss reports. Then as many as 76% of MSMEs in Gerung District also still use accounting information a little, this is because they do not know more information about the use of accounting information for MSMEs.